Carcinoma ex basal cell adenoma of the parotid gland: A report of an extremely rare case. Issue 7 (19th May 2017) - Kusafuka, Kimihide; Kawasaki, Takuya; Nakajima, Takashi; Sugino, Takashi
Abstract : Malignant non‐basaloid tumors that arise from basal cell adenoma (BCA) are extremely rare. The patient was a 72‐year‐old Japanese male, who had noticed swelling of the left parotid region 21 years ago. A superficial lobectomy was performed. About 60% of the tumor was made up of cribriform and trabecular tissue composed of basaloid cells, which exhibited mild atypia and nuclear expression of β‐catenin. This portion of the tumor was considered to be a BCA. In the other part of the tumor, the proliferation of large eosinophilic atypical cells, most of which formed intraductal structures, was observed. These tumor cells displayed cellular atypia, and some of them formed Roman bridge structures or contributed to intracapsular invasion. Immunohistochemically, these cells were positive for cytokeratin 7, gross cystic disease fluid proten‐15 (GCDFP‐15), androgen receptor (AR), and mammaglobin (MMG) and exhibited a high Ki‐67 labeling index. So, this portion of the tumor was considered to be a salivary duct carcinoma (SDC). The tumor's final diagnosis was SDC ex BCA (intracapsular type), which is extremely rare. GCDFP‐15, AR, MMG, and Ki‐67 are useful immunohistochemical markers for diagnosing SDC ex BCA.